RAGAM TRADISI PENJAGAAN AL-QUR’AN DI PESANTREN : (Studi Living Qur’an di Pesantren Al-Munawwir Krapyak, An-Nur Ngrukem, dan Al-Asy’ariyyah Kalibeber) - Anisah Indriati (STAI AL-ANWAR SARANG, 2017)
One of the most popular studies discussed in the Qur'anic study today is called living Qur'an. Although its phenomenological cultural nuances, but it is still included in the study of scriptures. Since living Qur'an is basically began from the phenomenon of the Qur'an in Every Day Life. This study discusses not focused on study of texts of the Qur'an, but in realm of the importance and practical function of the Qur'an in Muslim society. There are pesantrens of al-Qur'an which, in fact, make an important contribution in developing and improving Muslims interaction on the Qur'an. Their roles in creating hundreds or even more than thousands HuffÄáº“ al-Qur'an have proven their existences in living Qur'an. Many varieties of methods of and processes of the interaction have been done, so that Qur'an become into a live